2008
DOI: 10.3928/00989134-20081201-07
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychosocial Correlates of Fear of Falling Among Older Adults in Assisted Living Facilities

Abstract: Fear of falling is the most common reported fear among older adults. Nevertheless, little is known about whom among this population develops fear of falling and why. This study aims to identify physical and psychosocial correlates of fear of falling among older adults in assisted living facilities. Data were collected from interviews with 208 residents using measures of fear of falling, physical and social functioning, depression, and state and trait anxiety. Results revealed that 48.6% of the participants had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 31 publications
1
10
1
2
Order By: Relevance
“…Consistent with prior research (Filiatrault, Desrosiers, & Trottier, 2009; Ní Mhaoláin et al, 2012; Painter & Elliott, 2009; Sharaf & Ibrahim, 2008) we found that women were more likely to be fearful of falling. Conversely, we did not find that gender was associated with falls as it has been in prior studies (Hawkins et al, 2011; Painter & Elliott, 2009; Sharaf & Ibrahim, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior research (Filiatrault, Desrosiers, & Trottier, 2009; Ní Mhaoláin et al, 2012; Painter & Elliott, 2009; Sharaf & Ibrahim, 2008) we found that women were more likely to be fearful of falling. Conversely, we did not find that gender was associated with falls as it has been in prior studies (Hawkins et al, 2011; Painter & Elliott, 2009; Sharaf & Ibrahim, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, we did not find that gender was associated with falls as it has been in prior studies (Hawkins et al, 2011; Painter & Elliott, 2009; Sharaf & Ibrahim, 2008). This may due to sample selectivity.…”
Section: Discussioncontrasting
confidence: 87%
“…The relationship between depression and FOF is particularly relevant for older adult men, given the fact that analyses of veterans attending Veterans Administration gait and balance clinics have cited depression rates as high as 23% among male participants (Bishop, Meuleman, Robinson, & Light, 2007). Sharaf and Ibrahim (2008) found nearly identical predictors of FOF (balance, depression, and assistive-device use) in their study of 208 individuals living in assisted-living facilities compared with our community-dwelling participants.…”
Section: Discussionmentioning
confidence: 59%
“…Knowledge of any possible relationships between these factors contributes to the rehabilitation process by enabling clinicians to avoid fall incidents during training sessions. Studies have assessed FOF in the elderly population [9] and in persons with Parkinson disease [10] and stroke [11]. Lin et al investigated the kinematic, kinetic, and electromyographic aspects of postural control during falling with rapid reach-and-grasp balance reaction in individuals with thoracic (T) SCI wearing KAFOs [12].…”
Section: Introductionmentioning
confidence: 99%